GIRAFFE 3 als Zusatzmaterial der Schreibfertigkeit in der SMA N 11 Surabaya Klasse XII Semester 1 - NUR FADILAH, WAHYU (LATERNE, 2014)
This study Koran teaching materials problems. Background underlying this research study is a text book that can not be separated from education. The selection of textbooks is very important with regard to quality and in accordance with applicable curriculum (SBC). In an effort to determine the exposure of the material in the book writing skills Giraffe 3, therefore it is necessary to analyze the suitability of the book with the Education Unit Level Curriculum. The formulation of the issues discussed in this study is whether to book Giraffe 3 can be used as additional material for teaching writing skills in high school class XII Surabaya State 11 1st semester. Thus, this study aims to provide a description of any additional material writing skills. This study includes qualitative and descriptive research uses documentation method, because the authors conduct a content analysis. The data were obtained based on the book Giraffe 3, then collected, classified, and analyzed. Researchers used the theory of Hans Jürgen Krumm to determine whether the book Giraffe 3 in accordance with the criteria of good teaching materials. Example: a) The composition of the material, b) Layout c) Compliance with the curriculum; d) Contents and cultural knowledge; e) Language f) grammar; g) Exercise. From the results of this study (1) Giraffe Book 3 is categorized as a good textbook in accordance with the evaluation criteria of teaching materials. (2) Giraffe Book 3 in accordance with the Education Unit Level Curriculum and textbooks can be used as an adjunct in the German language teaching writing skills in high school German class XII 1st semester.